Rebranding strategy PT. Indonesia Building Solutions Plant Cilacap in forming brand awareness - Rohmah, Hani Fatkhur; Fajri, Choirul (COMMICAST, 2022)
The business world is increasingly showing developments with many new business actors appearing both on a small and large scale. The emergence of new business actors certainly has tightened business competition in the market so that it is not uncommon for businesses to close down because they do not have creative strategies to be able to compete. Rebranding is one of the strategies undertaken by business people to maintain their business. There are several factors that cause rebranding, such as changes in ownership, a brand that is starting to be forgotten, to a bad image in the eyes of the public, etc. Rebranding is tantamount to reshaping its brand awareness or public awareness of a new brand. PT. Indonesia Building Solutions is one of the companies that rebranded as a result of the acquisition by Semen Indonesia Group (SIG) of Holcim in January 2019. The acquisition process was followed by a change in all identities starting from the brand name, namely PT. Indonesia Building Solutions and the product name is dynamix. This research was conducted to determine how the rebranding strategy carried out by PT. SBI in forming brand awareness. The method used is descriptive qualitative by conducting direct research through interviews with related parties, documentation, field observations, and supporting data from the internet. Based on the research that has been done, PT. Indonesia Building Solutions rebranded with several stages, namely Repositioning, Renaming, Redesaigning, and Relaunching. With the implementation of these four stages, PT. Indonesia Building Solutions has achieved brand awareness at the brand recognition stage where there are still two more stages to be able to reach top of mind. The title of the research conducted by researchers is "The Rebranding Strategy of PT. Indonesia Building Solutions in Forming Brand Awareness "